MAGNETOOPTICAL PROPERTIES OF F-2(+) CENTER IN KCL-SH- - Donatti, D. A.; Aegerter, M. A.; Iida, T. (Akademie Verlag Gmbh, 1993)
The magnetic circular dichroism (MCD) of F2+ centers in KCl:SH- has been measured in absorption in the 1ssigma(g) --> 2p(y)pi(u) transitions at 493 and 509 nm, with fields up to 5 T and in the temperature range 1.5 K < T < 77 K. Within the limit of detection, no MCD is observed in the near infrared transition 1ssigma(g) --> 2psigma(u) as well as in both emissions 2ppi(u) --> 1ssigma(g) and 2psigma(u) --> 1ssigma(g). The optical detection of EPR in the F2+ ground state presents an isotropic single band with g = 1.965 +/- 0.007. The spin-lattice relaxation measured at H = 0.32 T is typical of a direct process T-1 = 4.3 x 10(-2_ coth (gmu(B)H/2k(B)T). The spectral variation of the MCD is calculated using perturbation theory to first order. The Hamiltonian includes the spin-orbit interaction in the 2ppi(u) excited state and the orbital molecular wave functions are obtained by a linear combination of 1s and 2p atomic orbitals. The calculated MCD is in good agreement with the observed one, for the spin-orbit interaction strength Pound(z) = 3.6 meV.